RELATIONSHIP BETWEEN HYPOTHALAMUS AND SEXUAL ORIENTATION - Checa, Alejandro; Alvear, Mercedes; Navas, Eliana; Córdova, Nathaly; Martínez, Briggitte; Tapia, William; Yánez-Ortiz, Érika (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Research on biological sexual differences in brain function, structure, and sexual orientation suggests links to prenatal androgen exposure, gender traits, and brain patterns, but findings remain inconclusive due to methodological challenges, inconsistent definitions, and societal or sampling biases. Objective: Determine if there is a relationship between the size of the hypothalamus and sexual orientation. Methods: This was a cross-sectional cohort study conducted between January 2022 and January 2023 at the Eugenio Espejo Specialties Hospital in Quito, Ecuador. Male subjects aged between 20 and 40 years participated. They were asked to reveal their sexual orientation and in the case of homosexual men, specify their sexual role as “active” or “passive”, the “versatile” did not participate in the study. The size of the hypothalamus was identified using simple MRI of the brain. Results: A total of 51 subjects were recruited, of which 40 self-identified as homosexual, of which 25 were passive and 15 active, the remaining 11 were defined as heterosexual. It was found that there is a statistically significant relationship between the size of the hypothalamus and sexual orientation with a p = <0.001. Conclusion: In our study, there is a statistically significant relationship between the size of the hypothalamus and sexual orientation. Keywords: Hypothalamus, sexual orientation, MRI, heterosexual, homosexual